691 Model online road safety training to municipal teachers in São Paulo, 2015. (1st September 2016) - Freitas, Gabriela
Abstract : Background: Beginning 2011, Criança Segura implemented an online safety course which trained more than 5, 000 people to date. The online course was developed to span the vast country and mobilise communities to take action on road safety. In 2015, we offered the training to public school teachers in the city of São Paulo, reaching 15, 000 people. Objective: To raise prevention culture on road safety through a partnership with São Paulo's Municipal Secretariat of Education. The 8-class online course includes national and regional data, background on prevention, educational support material and guidance on community mobilisation activities, in order to create a network of injury prevention multipliers. Results: This partnership with São Paulo's Municipal Secretariat of Education, the largest city in Brazil, leads us to improve results. The first 2015 class on Road safety trained 311 teachers, who implemented 195 community mobilisation activities, such as educational activities with children, families and school community, partnerships with public bodies to improve road safety in their neighbourhood, reaching over 15, 000 people with road safety information, in 3 months. 96% of the participants noticed behavioural changes towards road safety, 90% of them disclosed safety information to their own friends and family, 99% of them are motivated to continue the work as an injury prevention multiplier. Conclusions: In a time when access to information is disseminated through technology, Criança Segura believes in the online learning model, which has proven to be effective in promoting road safety and activating communities throughout a country. The partnering with public bodies may also become a model for an effective intersectoral action.